2005
DOI: 10.1007/s00421-005-1371-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface EMG and mechanomyogram disclose isokinetic training effects on quadriceps muscle in elderly people

Abstract: Maximum voluntary contraction (MVC) and cross-sectional area (CSA) of fast and slow twitch fibers are reduced in the lower limb muscles of elderly subjects. Isokinetic training at medium and high velocities has been widely used to improve muscle performance and force in young as well as elderly subjects. EMG and mechanomyogram (MMG) are compound signals in which the electrical and mechanical activities of recruited motor units (MUs) are summated. The aim of the present study was to verify the hypothesis that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…This increase is similar to that occurring on biceps brachii muscle, followed by a decrease in MMG RMS after 60% of MVC. Esposito et al (2005) showed for the VL muscle an increase in MMG RMS magnitude before of 80% MVC, and after this, the MMG RMS variation trended down. Similar results were found by Stock et al (2009) to RF, VL and VM (vastus medialis) muscles.…”
Section: Discussionmentioning
confidence: 99%
“…This increase is similar to that occurring on biceps brachii muscle, followed by a decrease in MMG RMS after 60% of MVC. Esposito et al (2005) showed for the VL muscle an increase in MMG RMS magnitude before of 80% MVC, and after this, the MMG RMS variation trended down. Similar results were found by Stock et al (2009) to RF, VL and VM (vastus medialis) muscles.…”
Section: Discussionmentioning
confidence: 99%
“…This signal, labeled "mechanomyogram" (MMG) to underline its mechanical origin, summates the activity from individual MUs. It has been suggested that the time and frequency domains of the MMG signal may provide information regarding the motor control strategies (MU recruitment and Wring rate) of various muscles during both isometric and dynamic muscle actions (Akataki et al 2003;Dalton and Stokes 1991;Esposito et al 1998Esposito et al , 2005Orizio 1993;Orizio et al 1989aOrizio et al , 1989bOrizio et al , 1990Orizio et al , 2003. SpeciWcally, it has been shown that MMG amplitude is related to MU recruitment, while the frequency content provides information about average MU Wring rate (Beck et al 2007;Orizio 1993;Orizio et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The EMG-MMG combined analysis was already applied to several muscle groups (Alves and Chau 2007;Esposito et al 1996Esposito et al , 2005Hwang 2007;Orizio et al 1997). This approach has been already utilized on FF muscles to detect diVerences in MU activation strategies between dystrophic patients and healthy controls (Orizio et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…OA causes a loss in force production capacity and reduced activation of the muscles that make up the quadriceps, leading to a mechanical overload of the joint due to the inability of the knee extensors to absorb impact during activities of daily living. 8 Various rehabilitation methods have been proposed to reverse the muscle weakness process. Among these, neuromuscular electrical stimulation (NMES) treatment has been used to reduce the risk factors associated with the development and aggravation of the degenerative processes of OA.…”
Section: Introductionmentioning
confidence: 99%